EVALUASI KONDISI BATERAI SISTEM HYBRID DI BARON TECHNO PARK - Ridwan Budi Prasetyo (Politeknik Harapan Bersama Tegal, 2021)
Abstract - The Baron Techno Park area is a model of an energy independent area that utilizes an electrical system based on a Hybrid Power Plant (Wind Energy and Solar Energy). The electrical system was built using an off grid system since 2011, by utilizing a battery of 120 cells @ 1200 Ah as energy storage. A battery system with lead acid battery (flooded battery) technology that has been operating for 10 years should be a concern. This makes a consideration for conducting research on evaluating the performance of a hybrid system battery. Voltage (V) and Specific Gravity (SG) measurements in no-load conditions are used as methods to see battery performance. Based on the measurement results, it is known that the average voltage and specific gravity are 2.074 volts and 1.160 g/ml. From the measurements, it is also shown that the 87th battery cell has the lowest performance, with an average voltage value of 2.023 volts and an average specific gravity of 1.099 g/ml.